Schools, accountability and transparency—approaching the Nordic school evaluation practices through discursive institutionalism. Issue 3 (2nd September 2018) - Wallenius, Tommi; Juvonen, Sara; Hansen, Petteri; Varjo, Janne
ABSTRACT: Over recent decades we have witnessed a growing emphasis on educational quality assurance and evaluation (QAE) around the globe. The trend, not only to intensify evaluative measurements, but also to publish school-specific indicators, has become visible also in the Nordic countries. In Sweden, Denmark and Norway, the governments have launched web-portals, in which various indicators can be observed and compared at the school level. However in Finland, the data is published only at a general level. In this article we compare the discourses of educational experts on comprehensive school QAE policies and practices in four Nordic countries, Sweden, Denmark, Norway and Finland. Our aim is to clarify how the discursive practices reflect the current evaluation and publication policies and how the discourses construct the rationales of educational governance. We have approached our data (58 interviews) from the framework of discursive institutionalism, which sees both the underlying ideas and beliefs, and the discursive practices as the dynamic factors behind institutional change. We argue, that in all the Nordic countries these discursive practices take place in a balancing discursive triad between global competence, neo-liberal accountability pressures and the traditions of the egalitarian Nordic comprehensive school—however with varying country-specific rationales on school accountability and transparency.